Topology Controlled Energy Proficient Protocol for Wireless Sensor Networks - Nehra, Vibha; Sharma, Ajay K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Random deployment in Wireless sensor networks lead to spatial node redundancy in close knit sensor networks. In this paper, an improved energy proficient PEGASIS based protocol (PEGASIS-TC) has been proposed. PEGASIS-TC exploits this spatial node redundancy by finding optimal subset of nodes that guarantee connectivity and turns off the remaining nodes based on CTR (Critical transmission range) to conserve energy which can be used in later stages to extend the network lifetime. The simulation results obtained show that PEGASIS-TC gives an increase in network lifetime as compared to PEGASIS.